Photothermal effects in fiber Bragg gratings. - Littler, I; Grujic, T; Eggleton, B (2006)
Writing a fiber Bragg grating in optical fiber generates an intrinsic broadband absorption term that can result in photothermal heating during subsequent use with fiber core guided light. This, in turn, can cause a significant shift of a grating resonance via the thermo-optic coefficient, even at low in-fiber light powers. The magnitude of the absorption term and its dependence on the grating strength are detailed. We further show how the degree of heating can be influenced by the particular environment in which the grating is placed and that, while the shift can be quite deleterious for some applications, its effect can be mitigated. A simple conductive model is developed.